The Philosophy of Existentialism: Individual Awareness in Indonesian Education: Filsafat Existentialisme: Kesadaran Individu dalam Pendidikan Indonesia - Purnama, Aditya Yoga; Putri, Agnesi Sekarsari; Saputri, Ragil (RADIANT: Journal of Applied, Social, and Education Studies, 2021)
The philosophy of existentialism emerged driven by the uncertain world conditions due to world wars. So existentialism is present as a thought movement that emphasizes human subjectivity and freedom. This study has a purpose for reflection. Reflection means the process of understanding events in the mind or experience that is owned. This study uses descriptive qualitative research. This study utilizes a literature search. The literature search process begins with key phrases such as â€œexistentialismâ€, â€œeducationâ€ and â€œawarenessâ€. Man must exist, which means realizing that he exists to control himself and act on his behalf. The philosophy of existentialism talks about human existence, while talking about humans means questioning educational issues. Each person is unique, which is different from one another. Realizing this is important for students, parents, teachers, principals, board members, and all those involved in education. Education is expected to realize the "intensity of awareness" of students. So that they are aware of their responsibility to determine the life they will live themselves. Â  Filsafat eksistensialisme muncul didorong oleh keadaan dunia yang tidak menentu akibat perang dunia. Sehingga eksistensialisme hadir sebagai gerakan pemikiran yang menonjolkan subjektifitas dan kebebasan manusia. Studi ini memiliki tujuan untuk refleksi. Refleksi berarti proses memahami peristiwa dalam pikiran atau pengalaman yang dimiliki. Studi ini menggunakan penelitian deskriptif kualitatif. Studi ini memanfaatkan pencarian literatur. Proses pencarian literatur dimulai frasa kunci seperti â€œeksistensialismeâ€, â€œpendidikanâ€ dan â€œkesadaranâ€. Manusia harus eksis yang artinya menyadari bahwa dia ada untuk menguasai dirinya dan bertindak atas nama dirinya. Filsafat eksistensialisme berbicara tentang keberadaan manusia, sedangkan berbicara tentang manusia berarti mempersoalkan masalah pendidikan. Setiap pribadi adalah unik yakni berbeda-beda satu dengan yang lainnya. Menyadari hal tersebut menjadi penting bagi seorang siswa, orangtua, guru, kepala sekolah, anggota dewan, dan semua yang terlibat didalam pendidikan. Pendidikan diharapkan dapat mewujudkan â€œintensitas kesadaranâ€ siswa. Sehingga sadar akan tanggungjawabnya untuk menentukan kehidupan yang akan dijalaninya sendiri.